PERAN MEDIA SOSIAL DALAM MENINGKATKAN JUMLAH KUNJUNGAN EKSIBISI INVESTASI BOGORFEST DI KABUPATEN BOGOR - Noorhayati, Susanti; Budianto, Irawan RD (PT. Media Edutama Nusantara, 2024)
ABSTRACT This research aims to determine the role of social media, especially Whatsapp, Facebook and Instagram, which are used as a means to promote the implementation of the Bogorfest investment exhibition by the Regional Government of Bogor Regency with the Leading Sector of the Bogor Regency Investment and One-Stop Integrated Services Service (DPMPTSP) in collaboration with government organizations. other areas. Bogor Regency has economic resources and natural resources that are potential for investment activities. It is very important for the community and related parties, especially the business world, to know complete and complete information on investment potential in Bogor Regency. As one of the strategies to promote Bogor, Bogor Regency uses events as strategic promotional media packaged in Bogorfest activities to showcase investment potential so that regional advantages can be known by the public, especially the business world from all sectors such as trade, agriculture, animal husbandry, industry, as well as various service. It is hoped that the participation of the business world in this event or exhibition will attract potential investors from domestic and foreign investors to invest in Bogor Regency. The increasing investment graph in Bogor Regency is influenced by the image of Bogor Regency which is good and ready to open itself to investors.